Loan activities and customer service satisfaction of Bangladesh Commerce Bank Limited (Pragati Sarani Branch) - Shafin, Md. Shahriar Kabir (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.